1975
DOI: 10.1084/jem.141.2.524
|View full text |Cite
|
Sign up to set email alerts
|

Competition between concanavalin A-induced stimulatory and inhibitory effects in the in vitro immune response to antigen.

Abstract: The humoral response of nude spleen cells (b cells) to sheep erythrocytes was measured in the presence of varying numbers of concanavalin A (ConA)-acvated stimulatory spleen T cells (helper) and Con A-activated inhibitory spleen T cells (suppressor) from BDF1 mice. It was found that suppressive effects could be reversed by the presence of additional numbers of stimulatory cells. These results seem incompatible with the hypothesis that suppression is mediated by supraoptimal numbers of stimulatory cells and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1976
1976
1979
1979

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Our data do not distinguish whether the effect of cellular concentration and period of cultivation on the response when cells are mixed is mediated directly by cell-cell interaction or via factors in the medium. The present work underlines the difficulty of interpretation and prediction of results in studies of the interactions between cell types in which different ratios of cells are mixed without also varying the total cell concentration or in which more than two sources of cells are mixed (43). Finally, this work illustrates that the function of cells ascertained in one set of conditions need not apply in a different cellular environment.…”
Section: Figurementioning
confidence: 90%
“…Our data do not distinguish whether the effect of cellular concentration and period of cultivation on the response when cells are mixed is mediated directly by cell-cell interaction or via factors in the medium. The present work underlines the difficulty of interpretation and prediction of results in studies of the interactions between cell types in which different ratios of cells are mixed without also varying the total cell concentration or in which more than two sources of cells are mixed (43). Finally, this work illustrates that the function of cells ascertained in one set of conditions need not apply in a different cellular environment.…”
Section: Figurementioning
confidence: 90%
“…However, similar experiments performed by Dutton (1973) led to different conclusions, based mainly on the fact that irradiation selectively eliminated suppressor but not helper T cells. Although it could be argued that irradiation simply reduced the number of T cells, it was later shown that this was not tbe case as dilution of the suppressor cells did not result in the appearance of helper effects (Scavulli & Dutton 1975).…”
mentioning
confidence: 99%
“…In addition HSA, an antigen without nonspecific mitogenic properties, had n o effect when injected simultaneously with AHGG. Nor can these results be explained by the production of a helper and suppressor T cell population, widely reported to be generated on lectin treatment [17][18][19][20] since Con A decreased AHGG trapping in the spleen of T celldeprived mice as well as normal mice (Table 4), and also because decreased uptake was found as early as 2 h after simultaneous injections of Con A and AHGG (Table 3), probably before any blast transformation occurred.…”
Section: Discussionmentioning
confidence: 99%